2020
DOI: 10.7759/cureus.10228
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Patterns of Salmonella Typhi and Salmonella Paratyphi in a Tertiary Care Hospital in Islamabad

Abstract: Background Enteric fever is a serious public health problem in Pakistan. Growing problem of drug-resistant Salmonella strains and outbreak of ceftriaxone-resistant Salmonella typhi in Hyderabad during 2016-2017 is concerning. This study aimed to determine the antibiogram profile of Salmonella typhi and Salmonella paratyphi isolated from blood cultures of patients presenting in Pakistan Institute of Medical Sciences (PIMS), Islamabad. Materials and methods A retrospective cross-sectional study conducted in PIMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
5
10
2
Order By: Relevance
“…among males. This finding is consistent with the studies done by Joshi et al and Umair and Siddiqui and likely reflects increased risk for this population, perhaps related to lapses in hygiene, particularly in lower age groups [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…among males. This finding is consistent with the studies done by Joshi et al and Umair and Siddiqui and likely reflects increased risk for this population, perhaps related to lapses in hygiene, particularly in lower age groups [ 10 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the resistance rates against amoxicillinclavulanate, gentamicin, and ciprofloxacin were 18.5%, 22.2%, and 33.3%, respectively. Umair and Siddiqui 27 from Pakistan (62.7%) and Katiyar et al, 28 from India (96.9%), reported higher resistance rates for ciprofloxacin compared to the current research. However, Katiyar et al 28 from India and Maharjan et al 29 The results of antibiotic resistance for Salmonella isolates are different in various countries, even in the diverse regions of the same country.…”
Section: Discussioncontrasting
confidence: 52%
“…S. typhi and Paratyphi strains are usually sensitive to third generation of cephalosporins but resistance is not uncommon. A study on enteric fever by Umair and Siddiqui[ 15 ] suggested that S. Paratyphi has less resistance pattern than S. typhi . The research also described that ceftriaxone and imipenem had lower chances of resistance, and the second one, respectively, is the most useful antibiotic in cases with resistant strains.…”
Section: Discussionmentioning
confidence: 99%